2020
DOI: 10.1101/2020.08.27.20183442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tocilizumab in Hospitalized Patients With COVID-19 Pneumonia

Abstract: BACKGROUND COVID-19 is associated with immune dysregulation and hyperinflammation. Tocilizumab is an anti-interleukin-6 receptor antibody. METHODS Patients hospitalized with severe COVID-19 pneumonia receiving standard care were randomized (2:1) to double-blinded intravenous tocilizumab 8 mg/kg or placebo. The primary outcome measure was clinical status on a 7-category ordinal scale at day 28 (1, discharged/ready for discharge; 7, death). RESULTS Overall, 452 patients were randomized; the modified-intention-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
187
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(197 citation statements)
references
References 21 publications
5
187
0
5
Order By: Relevance
“…39 Besides EMPACTA, the efficacy of tocilizumab in Covid-19 has been examined in one other randomized placebo-controlled trial, COVACTA. 35 . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
See 2 more Smart Citations
“…39 Besides EMPACTA, the efficacy of tocilizumab in Covid-19 has been examined in one other randomized placebo-controlled trial, COVACTA. 35 . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…[30][31][32][33][34] Although the randomized, placebo-controlled COVACTA trial-which enrolled patients with a range of disease severity, including 38% of patients receiving mechanical ventilation-did not meet its primary endpoint, its results suggested that tocilizumab may have a positive effect on recovery time and need for intensive care, which warrants further investigation. 35 The global phase III EMPACTA (Evaluating Minority Patients with Actemra) clinical trial investigated the safety and efficacy of tocilizumab in hospitalized, nonventilated patients with Covid-19 pneumonia, with an emphasis on enrolling high-risk and racial and ethnic minority populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RCT: No significant benefit 6. WHO temporarily paused trial for HCQ over safety concern but later resumed on June 03, 2020 7. US FDA emergency use approval revoked on June 15, 2020 HCQ and AZITHROMYCIN` K [ 53 , 67 , 84 94 ] 10 TOCILIZUMAB [ 95 , 96 , 98 – 100 , 106 ] Rheumatoid arthritis, and other inflammatory and autoimmune disorder IL-6 receptor antagonist 1. Retrospective study: Improve clinical presentations without significant side effects 2.…”
Section: Repurposed Therapeuticsmentioning
confidence: 99%
“…Random-effects meta-analysis showed no evidence of a difference between tocilizumab and control interventions on serious adverse events (RR 0.63; 95% CI 0.35 to 1.14; p = 0.12; I 2 = 77.4%; five trials; very low certainty) ( S55 Fig, S13 Table). either unclear [90,114], 28 days [111,113], or 30 days [112] after randomization. The trial sequential analysis showed that we did not have enough information to confirm or reject that tocilizumab versus control reduces the risk of serious adverse events with a relative risk reduction of 20%.…”
Section: Meta-analysis Of All-cause Mortalitymentioning
confidence: 99%